Enzymatic degradation of polylactide/layered silicate nanocomposites: Effect of organic modifiers - Singh N.K.; Purkayastha B.P.D.; Panigrahi M.; Gautam R.K.; Banik R.M.; Maiti P. (My University, 2025)
Biodegradable polylactide (PLA)/layered silicate nanocomposites have been prepared via solution route using two different kinds of organically modified nanoclays. The nanostructure as observed from wide-angle X-ray diffraction indicates intercalated hybrids and the extent of intercalation depends on the type of organic modifiers used. Melt-quenched PLA and its nanocomposites are predominantly amorphous but, after annealing, they are fairly crystalline. The nanohybrids show significant improvement in thermal properties as compared to neat polymer. The nature of interaction between nanoclays and matrix polymer depends on the organic modifiers used, as evident from varying heat of fusion and shifting of Fourier transform infrared peaks. The nanoclays act as nucleating agent, and thereby, control the spherulite dimension of the matrix. The comparison of biodegradation of PLA and its nanocomposites has been studied in enzyme, compost, and buffer solution. Biodegradability of PLA has significantly been enhanced in the presence of nanoclays and the rate varies on organic modifications. The surface morphology, before and after enzymatic degradation, confirms the relative rate of degradation through laser scanning confocal images, scanning electron microscope, and atomic force microscope. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Copyright © 2012 Wiley Periodicals, Inc.